Study of prevalence and pattern of dyslipidaemia in type 2 diabetes mellitus patients attending rural health training centre of medical college in Bhopal, Madhya Pradesh, India - Borle, Amod L.; Chhari, Neeraj; Gupta, Girjesh; Bathma, Vishal (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes is endemic globally with increasing prevalence in both developing and developed countries. Persistent hyperglycaemia of diabetes is associated with micro as well as macro vascular complications like coronary heart disease, stroke, diabetic renal disease, diabetic retinopathy and neuropathy etc. Dyslipidemia contribute to considerable increased risk of atherosclerosis and consequent mortality in diabetic patients. It often precedes onset of diabetes particularly type 2 DM and may persist inspite of adequate control of blood sugar. The objective of the study was to study prevalence and pattern of dyslipidemia in type 2 diabetes mellitus patients attending Rural Health and Training Centre of medical college in Bhopal, Madhya Pradesh. Methods:This was a cross sectional study carried out among 50 Type 2 diabetic mellitus patients attending OPD of Rural Health Training Centre (RHTC) of medical college in Bhopal Madhya Pradesh. Study population included known as well as newly diagnosed type 2 diabetic patients more than 30 years of age attending OPD at RHTC. Results: According to ATP III guidelines dyslipidemia was observed in 43 (86%) study subjects. Hypercholesterolemia was seen in 18 (36%) study subjects. Increased LDL and triglycerides was observed in 33 (66%) and 32 (64%) study subjects respectively. Lower HDL cholesterol values were observed in 26 (52%) study subjects. Out of 43 study subjects having dyslipidemia, 14 (32.6%) study subjects were having isolated single parameter dyslipidemia, while 10 (23.2%) had combined two parameter dyslipidemia and 19 (44.2%) study subjects showed mixed dyslipidemia. Conclusion: Results suggest high (86%) prevalence of dyslipidemia among type 2 diabetes mellitus study subjects. Most common pattern observed was mixed type dyslipidemia. These lipid abnormalities might be the important in view of development of cardiovascular or cerebrovascular diseases. Hence type 2 diabetic patient should undergo the routine monitoring of blood sugar and lipid profile so that any abnormalities can be identified and preventive measures along with interventions can be initiated at the earliest.